BCOR‐CCNB3 fusion‐positive clear cell sarcoma of the kidney. Issue 4 (26th December 2019) - Han, Hyojeong; Bertrand, Kelsey C.; Patel, Kalyani R.; Fisher, Kevin E.; Roy, Angshumoy; Muscal, Jodi A.; Venkatramani, Rajkumar
Abstract: Clear cell sarcoma of the kidney (CCSK) is the second most common malignant pediatric renal tumor. Two of the recurrent somatic alterations reported in CCSK are BCL‐6 corepressor (BCOR) internal tandem duplication (ITD) and YWHAE‐NUTM2B/E gene fusion. A minority of patients with CCSKs have other rare somatic alterations. We report two patients with CCSK showing BCOR‐CCNB3 (where CCNB3 is cyclin B3) fusion, who had similar clinical presentation of a large renal mass with tumor thrombus extending through the inferior vena cava into the right atrium and a favorable response to chemotherapy. We recommend BCOR‐CCNB3 fusion testing for all patients with CCSK who lack BCOR‐ITD or YWHAE‐NUTM2B/E gene fusions.